Development of a lytic Ralstonia phage cocktail and evaluation of its control efficacy against tobacco bacterial wilt - He, Haoxin; Yi, Ke; Yang, Lei; Jing, Yongfeng; Kang, Lifu; Gao, Zhihao; Xiang, Dong; Tan, Ge; Wang, Yunsheng; Liu, Qian; Xie, Lin; Jiang, Shiya; et al. (Frontiers in Plant Science, 2025)
IntroductionBacterial wilt (BW) caused by Ralstonia pseudosolanacearum is a devastating soil-borne disease. Bacteriophages are important biocontrol resources that rapidly and specifically lyse host bacteria, showing good application potential in agricultural production.MethodsThis study isolated nine phages (YL1–YL9) and, using host range and pot experiments, identified two broader host range phages (YL1 and YL4) and two higher control efficacy phages (YL2 and YL3), which were combined to obtain five cocktails (BPC-1–BPC-5).ResultsPot experiments showed that BPC-1 (YL3 and YL4) had the highest control efficacy (99.25%). Biological characterization revealed that these four phages had substantial thermal stability and pH tolerance. Whole genome sequencing and analysis showed that YL1, YL2, YL3, and YL4 belonged to the genus Gervaisevirus. AlphaFold 3 predictions of tail fiber protein II structures showed that YL1 differed significantly from the other phages. Amino acid sequence alignment revealed that the ORF66 (YL1) “tip domain” of contained a higher proportion of aromatic and positively charged amino acids. However, the surface of the ORF69 (YL4) “tip domain” exhibited more positively charged residues than ORF66 (YL2) and ORF70 (YL3). These characteristics are hypothesized to confer a broader host range to YL1 and YL4.DiscussionThis study demonstrates that phages assembling a broad host range and high control efficacy have better biocontrol potential, providing high-quality resources for the biological control of BW.